Structural Characterization of a New Magnesium Oxysulfate Hydrate Cement Phase and Its Surface Reactions with Atmospheric Carbon Dioxide. Issue 11 (30th August 2013) - Runčevski, Tomče; Wu, Chengyou; Yu, Hongfa; Yang, Bo; Dinnebier, Robert E.
Abstract : A new magnesium oxysulfate hydrate phase, 5Mg(OH)2 ·MgSO4 ·7H2 O was synthesized and structurally characterized. The new phase crystallizes in the form of microsized needles and its crystal structure was solved using X‐ray powder diffraction. The crystal packing is made of infinite triple MgO6 chains, intercalated with sulfate groups, water molecules, and hydroxide anions. Using vibrational spectroscopy [infrared (IR) and Raman] and Rietveld refinement, the arrangement of water molecules and hydroxide anions were observed to be statistically distributed and dynamically disordered. The high‐temperature behavior and decomposition were studied by thermal analyses and in situ X‐ray powder diffraction. The high‐temperature measurements reveal the presence of five decomposition stages from the new phase to the production of MgO. After the reactions with atmospheric carbon dioxide were analyzed using micro‐Raman spectroscopy, two new carbonate phases were detected on the surface of the material.